DINAMIKA KONFLIK DAN PERDAMAIAN ACEH - Hany Nurpratiwi (Universitas Negeri Gorontalo, 2019)
The roots of the conflict in Aceh have been seen since the days of the feodal. Conflicts in Aceh not only occur with the central government, but Aceh has internal conflicts within the government. The reign of Sultan Iskandar Muda has divided the Aceh region into two groups, Uleebalang and Ulama. Allegedly the two groups already have a relationship that is not harmonious. Entering the period of Indonesian independence, the conflict in Aceh could not be resolved despite several peace compromise actions. Aceh's internal conflicts during independence occurred between Islamic groups and secular groups related to the Aceh government system. In addition to these internal conflicts, Aceh also has conflicts with the central government. The Acehnese feel that the central government is not paying attention to their well-being, causing a lot of poverty. Efforts to resolve conflicts in Aceh with the central government have been carried out by granting regional autonomy and political autonomy to the Special Region of Aceh.